Srednješolske književne vsebine na recepcijskem situ - Žbogar, Alenka (Jezik in slovstvo, 2003)
The article elucidates the complexity and responsability of the process of choice and differentiation in high school literary themes. The criteria that need to be taken into consideration are provided. Theoretical starting-points of the reception theory, literary didactics and literary theory (short stories and novels to be more concrete) and the results of an experiment carried out with 4th year grammar school and vocational school pupils were used when creating the criteria. A presentation is made on what younger and older teenagers like to read, and for the later also how they read. The article concludes with concrete proposals of literary texts (short stories and novels) and notions for interpretation, differentiated according to various levels (first nad fourth year), and educational programmes (grammar school and four-year vocational school).
Keywords: književnost; literature; didactic method; didaktika; literarna teorija; literary theory; srednje šole